Prevailing factors influencing the use of Alcohol among Motor cycle Riders in Ikenne local Government in Ogun State .Nigeria - Oyerind, Makinde,Bose , Awomodu Damilola; Ayodele, Adeoye (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
There has been global concern over road traffic injuries. According to the World Health Organizations (2004), one-quarter of injury fatalities are due to traffic crashes with 90% occurring in low- and medium-income countries. Many countries in Africa, including Nigeria, are considered low and medium countries. A descriptive survey method design was used in carrying out this study. A total sample of 230 motorcycle riders in Ilishan-Remo Ogun State wre administered 230 questionnaires and the response rate was 100%. The data collected was analysed using descriptive statistics such as percentages tables and chart. From the study, it is apparent that majority of the respondents were exposed to alcohol at a very tender age between 15-24years of age, they take alcohol daily. Obviously they are addicted to alchol and they cannot go a whole day without alcohol consumption. Majority of the respondents 142(61.8%) are aware of the health hazards associated with alcohol consumption and 104(45.3%) are aware that excessive alcohol could cause liver trouble. It was alsorevealed that majority of the respondents 126(54.7%) spend most of their daily income on alcohol and as such affects their socio-economic status. It was revealed that the majority of the respondents126(54%) tried to quit drinking for a period of time and started back in a day or two. There is therefore a need for an effective intervention/ programmes to enlighten them or expose them to the implications of alcohol consumption.